If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(e + 2) = 12 Reorder the terms: 2(2 + e) = 12 (2 * 2 + e * 2) = 12 (4 + 2e) = 12 Solving 4 + 2e = 12 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2e = 12 + -4 Combine like terms: 4 + -4 = 0 0 + 2e = 12 + -4 2e = 12 + -4 Combine like terms: 12 + -4 = 8 2e = 8 Divide each side by '2'. e = 4 Simplifying e = 4
| s^3+9*s^2+26*s+24=0 | | 20t^2-4t^4= | | 10z+12=8z | | 15x-15=x+9 | | 3log=1.5 | | 4w^2+25w+36= | | s(s+7)(s+9)(s+10)(s+15)=0 | | (u-6)(u+4)=-21 | | 32-98n^2=0 | | 6c+4=-3c-14 | | 900=5[x+(x+14)] | | 20(s+2)(s+3)(s+6)(s+8)=0 | | -30=-2x-15 | | C^2+4-45= | | 8x+4y=180 | | x/4-=8 | | 0.9354=638*X+1.087 | | 900=5[x(x+14)] | | a=2pi(6)(14) | | 7x-5+2x=4 | | x^2+8x+3y+13=0 | | 11x+3y=1 | | 7x+-13x=-1+23 | | 3+tan^2x=5tanx | | 4(-2/3) | | h=3.5 | | 4cos^2x-3cosx=1 | | 5x+10y=1 | | 3b^2-3b-15= | | c=110+85h | | 3x-6y=-24 | | 4.25x+5.90(151-x)=734.15 |